Characteristic evaluation of geopolymer based lateritic soil stabilization enriched with eggshell ash and rice husk ash for road construction: An experimental investigation - Anburuvel, A.; Sathiparan, N.; Anuradha Dhananjaya, G.M.; Anuruththan, A. (Elsevier, 2023)
In line with sustainable development, the road sector has initiated the use of agro-wastes in road construction to preserve natural resources, which have been commonly used in conventional construction. In that sense, this study investigates the merits and demerits of incorporating eggshell ash (ESA) and rice husk ash (RHA) into geopolymer based lateritic soil stabilization for roadbase construction. Atterberg limits, modified Proctor compaction, unconfined compressive strength (UCS) tests were conducted on lateritic soil samples stabilized with cement or geopolymer that comprises of the combination of ESA, RHA and sodium hydroxide solution (NaOH). Results from the experimental study revealed that an increase in ESA substitution level reduced the plasticity index of lateritic soil. Maximum dry density was slightly reduced in all soil mixes stabilized with ESA, RHA and NaOH. With reference to cement stabilization, UCS showed a marginal reduction of 8.2 and 13.2% in geopolymer combinations of 3E1R1N (3% ESA + 1% RHA + 1% NaOH) and 2E2R1N (2% ESA + 2% RHA + 1% NaOH), respectively. Notably, out of all mixes, the mix combination of 3E1R1N and 2E2R1N produced the lowest cost to strength and embodied energy to strength ratio, and relatively lower CO2 emission to strength ratio. The authors believe that the proposed geopolymer stabilization method would be a competitive alternative to cement based lateritic soil stabilization for roadbase construction.
Keywords: Eggshell; Rice husk ash Road; Base; Soil stabilization; Unconfined compressive strength